BIOLOGICAL FITNESS COSTS OF GLUTATHIONE-S-TRANSFERASE (GST)-MEDIATED PERMETHRIN RESISTANCE IN ANOPHELES GAMBIAE GILES (DIPTERA: CULICIDAE) - Adesoye, Oluwaseun Adegbola; Adeogun, Adedapo O.; Oyeniyi, Tolulope A.; Olagundoye, Olalekan E.; Izekor, Romoke T.; Adetunji, Oluwakemi O.; Babalola, Ayodele S.; Akinsete, Israel O.; Adeniyi, Kamoru A.; Akinleye5Callistus A.; Adediran, Adewale D.; Isaac, Chidima; et al. (FUDMA JOURNAL OF SCIENCES, 2024)
Glutathione-S-transferase (GST)-mediated resistance development has been well documented in Anopheles gambiae Giles (Diptera: Culicidae). However, its biological consequences in this malaria vector are merely addressed. The present study aims to determine the implications of such a response in An. gambiae Kisumu population following exposure to a concentration of permethrin selection across multiple generations. Generations of adult mosquitoes exposed to 0.2 µg/bottle of permethrin were compared with unexposed controls to analyze resistance development, life events, and GST levels. Data obtained were analyzed using SPSS. Analysis of Variance was used to determine statistical differences at 95%. Resistance development and inference on filial generation where the population becomes resistant to recommended concentration (full-blown resistance) were determined using the R-Program. The fecundity of the selected population declined progressively over generations. With an increase in the activity of GST enzyme as stated in the previous study, the resistance of the Kisumu population progressed significantly (P = 0.041) against 5.0 µg/bottle and 10.0 µg/bottle from f1 to f4 generations in response to generational selection by 0.2 µg/bottle. This population would infer full-blown resistance at the 154th generation as a result of generational exposure to 0.2 µg/bottle. Mosquito resistance development is detrimental to malaria vectors as it reduces oviposition capability, increases the longevity of immature stages with filial generations, and delays full-blown resistance of susceptible vectors.